Neoadjuvant Therapy for Pancreatic Ductal Adenocarcinoma: Where Do We Go? - Wang, Chenqi; Tan, Guang; Zhang, Jie; Fan, Bin; Chen, Yunlong; Chen, Dan; Yang, Lili; Chen, Xiang; Duan, Qingzhu; Maimaiti, Feiliyan; Du, Jian; Lin, Zhikun; et al. (Frontiers in Oncology, 2022)
The incidence of pancreatic ductal adenocarcinoma (PDAC) has been on the rise in recent years; however, its clinical diagnosis and treatment remain challenging. Although surgical resection remains the only chance for long-term patient survival, the likelihood of initial resectability is no higher than 20%. Neoadjuvant therapy (NAT) in PDAC aims to transform the proportion of inoperable PDACs into operable cases and reduce the likelihood of recurrence to improve overall survival. Ongoing phase 3 clinical trial aims to validate the role of NAT in PDAC therapy, including prolongation of survival, increased R0 resection, and a higher proportion of negative lymph nodes. Controversies surrounding the role of NAT in PDAC treatment include applicability to different stages of PDAC, chemotherapy regimens, radiation, duration of treatment, and assessment of effect. This review aims to summarize the current progress and controversies of NAT in PDAC.